THE ERYTHROCYTE MEMBRANE ENDURANCE AGAINST TISSUE ISCHEMIA IN PATIENTS WITH HYPERTENSIVE DISEASE AND ISCHEMIC HEART DISEASE AND ITS RELATIONSHIP WITH ENDOGENOUS FACTORS - A. S. Sergeeva; Yu. I. Pivovarov; T. E. Kurilskaya; E. E. Kuznetsova (Российский кардиологический журнал)
Aim. To find out the type of erythrocyte membrane endurance to local ischemia in patients with AH and AP including its relationship with endogenous factors. Material and methods. Totally 60 men included with stable form of angina pectoris and 50 men with hypertension of the age 40-55 y.o. To compare the relationships that were found with normal values the parameters studied also were measured in healthy men (n=20) at the age 27±2,5 y.o. The prominence of changes in erythrocyte membrane was evaluated by their comparison before and after local ischemia. In every patient the endurance index (index(m)) was calculated for the erythrocyte membrane. Then we studied endogenous factors that modified the shifts of erythrocyte membrane endurance in the patients studied.Results. During the study it was shown that the erythrocyte membrane endurance to tissue ischemia in AH and AP patients was significantly lower comparing to healthy males. Also in patients there was relation between shifts of membrane endurance and baseline level of various endogenous factors activity. In AP patients the endurance of membrane could be modified by five predictors: blood viscosity in moderate diameter vessels, ACE and less von Willebrand factor. In both groups the increase of baseline ACE and blood viscosity was followed by the decrease of membrane endurance. But if the ischemia developed at the background of weak ACE activity or low blood viscosity, then erythrocyte membrane was more endurable to this pathogen factor.Conclusion. The relationships found for endogenous factors and membrane endurance, it seems, shows differences in genesis of angina pectoris and hypertension. The relations require confirmation in other patients selections with the same pathology and only then can be used for the development of further findings of the main pathogenetic chains in the patients with AH and AP, as for additional treatment strategies development.